Pemberdayaan Pekerja Seks Komersial (Psk) Di Komplek Pembatuan Banjarbaru Kalimantan Selatan - M. Adriani Yulizar, Wahyuddin dan (IAIN Antasari Banjarmasin, 2014)
This study aims at assessing the implementation of the empowerment program of commercial sex workers through community development at the Pebatuan localization complex in Banjarbaru which has been undertaken by PusatPengabdianMasyarakat (PPM) IAIN Antasari Banjarmasin. It is identified from the result of the study that the empowerment program is considered effective. The empowerment program effectiveness is indicates from: the benefits of religious sermon, the suitability of the sermon material, the sermon attraction, the ability of the preacher, the sermon duration, the trainings benefits, the trainings suitability, the ability of the trainer, the trainings duration, the trainings skills, the awareness to participate in the trainings, the trainings facilities, the suitability of the trainings equipment, the program sustainability, the need to continue the programs, the programs committee services, the committee clarity, the employersâ support to participate in the sermon, the employersâ support to participate in the trainings, the will to change the way of life, the belief of changing fate, and the will to develop the trainings. Moreover, there is a significant correlation between the related variables which includes the religious sermon activities, the trainings activities, the facilities, the awareness to participate in the trainings, the employersâ supports, and the belief and will of the participants and the committee services. However, some weaknesses of the variables are also found, namely: the lack of facilities provided, the lack of ability of the trainers, the lack of skills given in the trainings, the lack of duration of the sermon and trainings.